ANALISIS HUMAN CAPITAL DALAM UPAYA MENCAPAI KINERJA PERUSAHAAN PADA BOLU AMOR BAKERY & CAFE SUKABUMI - Agung Vitara Darma; Erry Sunarya; Kokom Komariah (STIE DWI SAKTI BATURAJA, 2022)
This research was meant to analysed Human Capital in Bolu Amor Bakery and Cafe Sukabumi addition andimprove the companies with the management of Human Capital in the improvement of companies. Thisresearch using the research methodology of descriptive-qualitative research to describe the human capitalcondition. For data collecting used observation instrument, interview, and documentation study methods.The results showed that the company gives a Human Capital Management with an integrated and continousmethods to achieve a long-term world Class Company vision. There are HCR, OCR, and employee productivity.This company has implemented 5 Human Capital components. There are individual capability, individualmotivation, the organizational climate, workgroup effectiveness and leadership. But, that haven’t maximalyet due to company leadership indicator still get some problems in process. Based on the results, we got theconclusion that Bolu Amor Bakery & Cafe Sukabumi has realized how important Human Resources in everyactivity. Company should manage the human resources well because the key of company success is in humanfactor. Not only in technology superiority and fund available. So, we need a capable person that can operatethe company as a survivor. Preparing the human capital is a must for improvement of companies.